eXSRUP: Hybrid Software Development Model Integrating Extreme Programing, Scrum & Rational Unified Process - Nidhi Sharma; Manoj Wadhwa (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Software industries are progressively adopting the agile development practices of customized models such as Extreme Programming (XP) or Scrum or Rational Unified Process (RUP). Scrum and Extreme Programming (XP) are frequently used agile models, whereas Rational Unified Process (RUP) is one popular classic plan driven software development methodology. Both agile and plan driven models have their own merits & demerits such as XP has good engineering practices, team collaboration and on the other hand weak documentation, poor performance in medium & large scale projects. Scrum is based on project management practices. RUP model has some limitations such as impractical for small and fast paced projects, tendency to be over budgeted, condemn rapid changes in requirements. This research paper based on proposes hybrid framework eXSRUP by combining strengths of Scrum, XP and RUP by suppressing their limitations to produce high quality software.